2007
DOI: 10.4103/1319-3767.36746
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics and irritable bowel syndrome in Shiraz, Southern Iran

Abstract: Due to the high prevalence of anxiety and depression in patients with IBS, psychotherapy and pharmacotherapy of these patients is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…By contrast, in some earlier studies, higher neuroticism scores have been reported in patients with IBS than in subjects without IBS [10,11]. A possible major reason for the absence of any significant difference in the neuroticism score between subjects with and without IBS in our study was that the subjects were all freshmen college students.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…By contrast, in some earlier studies, higher neuroticism scores have been reported in patients with IBS than in subjects without IBS [10,11]. A possible major reason for the absence of any significant difference in the neuroticism score between subjects with and without IBS in our study was that the subjects were all freshmen college students.…”
Section: Discussioncontrasting
confidence: 96%
“…In the study conducted in 41 IBS patients and 2000 healthy persons aged 41 to 49 years old by Palmer et al using [10] Eysenck’s index (Maudsely Personality Inventory: MPI), the average score for neuroticism was higher in the IBS patients than that in healthy persons. In a study performed in 60 IBS patients (average age ± standard deviation: 29 ± 7) and 55 healthy persons (average age ± standard deviation: 27 ± 7) using the Minnesota Multiphasic Personality Inventory (MMPI-2), Mousavinasab et al [11] reported a higher average score for hypochondriasis in the IBS patients than that in the healthy persons. Farman et al [12] showed that the average score for neuroticism in an evaluation conducted using the NEO Five-Factor Inventory (NEO-FFI) was significantly higher in the C-IBS group (33 patients) than the scores in the groups with other subtypes of IBS (71 with D-IBS patients and 46 A-IBS patients).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the MMPI-2 has been validated in Iran (Duckworth & Anderson 1995;Haskell, 1996;Mokhber et al, 2008;Mootabi, 1995). Therefore, the MMPI-2 is mostly applied as the standardized test for screening of mental and personality disorders in Iran (Khodarahimi, 2010b;Mootabi, 1995, Mousavinasab et al, 2007. This study only used the four subscales of MMPI-2 that measure the psychopathic deviation (PD).…”
Section: Buss-perry Aggression Questionnaire (Bpaq)mentioning
confidence: 99%
“…It is one of the commonest disorders diagnosed by gastroenterologists (8, 9). There is a large part of the population suffering from IBS while only some seek health care in the absence of curative therapy (6, 7, 9, 10). The prevalence of IBS usually varies significantly between countries and depends on the diagnostic criteria used (11).…”
mentioning
confidence: 99%